Faktor-Faktor Jasa Pelayanan yang Memengaruhi Kepuasan Konsumen di Bank Pembangunan daerah Bali - Berata, Dewa Ayu Novitasari; Supriyadi, Supriyadi (Jurnal Psikologi Udayana, 2016)
This research had been done in Bank Pembangunan Daerah Bali which is in the several branches have reduction of consumers saving percentage. In early of 2014, the asset position of BPD Bali was Rp. 14.763.000.000.000,00. But in facts said that the quantity of consumers saving have a significant reduction. It means, there are many consumers of Bank Pembangunan Daerah Bali are not satisfied with the services of the bank. The research goal is to find the empirical data about how much factors of service’s contribution to the consumers satisfaction of Bank Pembangunan Daerah Bali. This research used quantitative research method. The analysis method used discriminant analysis. The subject of the research is the consumers of Bank Pembangunan Daerah Bali, which have been chosen from 3 branches, those are  Mangupura branch, Denpasar (Gajah Mada) branch, and Klungkung branch. Criterias of the subject are the consumers which in 20 until 60 years old and had been the consumers of Bank Pembangunan Daerah Bali more than a year. The technique of data collection is giving the questionaire of the consumers satisfaction scale to the consumers who are qualified. The result or the research show that there are three factors of services which has contribution to the satisfaction of Bank Pembangunan Daerah Bali consumers. Those factors are the physical evidence of service, responsiveness of service, and perception factor. The service factors that has the biggest contribution to the consumers satisfaction is physical evidence of service with relative contribution in the mount of 87,6%, it followed by the perception factors with relative contributin  as big as 38,6%, and responsiveness of service with relative contribution in the mount of 30.8%. Believed that three aspects could predict the satisfaction level of the consumer together, with the same effective contribution as big as 52,6%. Satisfaction, Banking Services, Saving Clients Of Bank Pemerintah Daerah Bali.